Local economic development in Ghana: From the 'lost decades' to a policy 'maturing' stage. Issue 5 (3rd September 2017) - Mensah, James Kwame; Bawole, Justice Nyigmah; Ahenkan, Albert
ABSTRACT: Analysis and studies of local economic development (LED) tend to be under the rubric of case studies to the neglect of their historical context and the role of international development agencies. This article attempts to fill this gap by focusing on the experiences of Ghana. Adopting a systematic review of the policy documents and existing literature, it was found that, despite its significance, LED was not the priority of the governments of pre and post immediate independence era. In the fourth republic of Ghana, LED gained prominence in the various policy documents but this appears to be rhetoric and camouflage because they have not seen real implementation. However, international development agencies have played a significant role in initiating, funding and implementing specific LED activities in the various districts in Ghana. Overall, LED in Ghana has crawled from the 'lost decades' to a policy 'maturing stage'.